Evaluation of the Effectiveness of the Village Food Safety Movement Programme in Improving the Knowledge, Attitudes and Behaviour of Family and Community Cadres in North Sumatra - Eliska, Eliska; Ramadhani, Lutfiah; Hariyanti, Atika Ayu; Novi, Salwa Luthfiyyah; Sagala, Alisa Ariani; Mahira, Clarissa Bunga; Br Ginting, Hermalia Putri (Preventif : Jurnal Kesehatan Masyarakat, 2025)
This study examines the impact of the Village Food Safety Movement (GKPD) program initiated by BPOM in improving the knowledge, attitudes, and behaviors of food safety cadres in stunting and non-stunting villages in North Sumatra. The aim of the study was to evaluate the effectiveness of the GKPD intervention on food safety understanding and practices among cadres. The method used was a retrospective analysis with data from pre-test and post-test surveys on cadre groups in six villages during the period January to December 2022. The results showed that there was a significant increase in cadres' knowledge on food safety, with an average increase in general knowledge from 26.5% to 57.4% after the intervention. In addition, attitudes and behavioral aspects also showed progress, although some areas such as food processor hygiene still require more attention. In conclusion, the GKPD program is effective in increasing cadres' awareness and ability to manage food safety, which is expected to contribute to food security at the village level.